Crystallographic modeling and impedance studies of gadolinium modified La1−xGdxMnO3 (x = 0.1–0.3) ceramics. (10th January 2017) - Chourasia, Rashmi; Varma, Vijay; Chaurasiya, Shivendra; Shrivastava, O.P.
Graphical abstract: The refinement plots represent a structure fit between observed and calculated intensity with satisfactory R -factors. The cell volume and La–O, Mn–O bond distances resister a slight decrease with increase of gadolinium content. Impedance spectroscopic studies of the material suggest relaxation effects of Debye type. The relaxation frequencies shifted to higher frequency side with increase in temperature. The complex impedance plots reveal the main contribution of bulk phase in the electrical properties of the material. The variation of bulk a.c. conductivity as a function of temperature demonstrates that the compound exhibits semiconductor behavior. Abstract: The crystal chemistry of perovskite structured ceramic phases: La0.9 Gd0.1 MnO3 (LMGd-1), La0.8 Gd0.2 MnO3 (LMGd-2) and La0.7 Gd0.3 MnO3 (LMGd-3) have been investigated using General Structure Analysis System (GSAS) programming. The LMGd phases crystallize in the space group R -3 c and Z  = 6. Powder diffraction data have been subjected to Rietveld refinement to arrive at a satisfactory structural convergence of Rietveld parameters: R p, R wp and goodness of fit. Lattice parameters, bond lengths and bond angles have been calculated from GSAS software. Their electrical behaviour investigated by impedance spectroscopy in the frequency range 42 Hz–5 MHz at temperatures between 50 ° and 300 °C. Nyquist plots show the dominance of grain contribution and Debye – like relaxation in the materials. Conductivity data as a function of temperature and frequency suggest semiconductor behavior of the materials.